Cultivating a New Field at the Boundary Between Geoscience and Education Research. Issue 1 (25th August 2021) - Kastens, Kim A.
Abstract: I was privileged to contribute to the creation of a new field, Geoscience Education Research. This liminal field, with roots in both education research and geosciences, is deepening how people think and learn about the Earth. In this article, I recount some of my twists and turns along way, and ponder whether such a zig‐zagging pathway was essential or a distraction. And if essential, what made it possible? Twenty‐first century geosciences aporous boundaries, with insights flowing in and out from health sciences, social sciences, humanities, business, and other physical sciences. Such boundary regions are fertile ground for both basic and use‐inspired research. If you feel drawn to a boundary region, perhaps my story can provide encouragement or advice. Plain Language Summary: Geoscience Education Research investigates how experts and students think and learn about the Earth. The field is a hybrid: deeply informed by the priorities, worldview, knowledge and practices of Geoscience, but applying research methods derived from cognitive and learning sciences. This memoir tracks the emergence of this young field as seen through the eyes of one of its early practitioners. Key factors in this emergence were: the willingness of a few expert geoscientists to become "boundary crossers" and venture into serious education research, several pivotal multidisciplinary convenings, wisdom shared from cognitive and learning scientists, and a system of professional development workshops ready to transfer research insights into practice. Key Points: The emerging field of Geoscience Education Research (GER) investigates how humans think and learn about the Earth GER was founded by boundary crossers, informed by older disciplines, and shaped by the inherent characteristics of our complex, ancient, heterogenous, life‐supporting planet A career path that crisscrosses intellectual boundaries presents challenges, but can enable synthesis of new insights that draw from multiple domains